A new-type composite film of cholesteric liquid crystal doped with PCBM for laser-damage prevention in both visible and near-infrared region. (13th October 2017) - Zhao, Yuzhen; Tian, Shaopeng; Wang, Zhendong; Zhu, Min; Ren, Huaping; Ma, Qiang; Guo, Zhun; Li, Kexuan; Ding, Siyi; Miao, Zongcheng
ABSTRACT: Nowadays, with the increasing use of high-power laser, research and development of laser-damage prevention materials with multifunctional features and wideband wavelengths are urgent and indispensable. In the paper, cholestric liquid crystal (ChLC) is first proposed to be doped with a high-efficiency optical limiting material, 6, 6-phenyl C61-butyric acid methyl ester (PCBM), to fabricate a new-type laser-damage-prevention film. The ChLCs have the desired reflection wavelengths covering 750–2300 nm, which is an effective and potential candidate for the prevention of continuous or tuneable laser in near infrared (NIR) region. Meanwhile, the solubility of PCBM in LC and its nonlinear absorption property of are discussed, and it was proved that the good solubility of PCBM in LC contributed to the excellent nonlinear absorption of mixture (LC doped with PCBM). Taking advantages of this phenomenon, a novel composite film of ChLCs doped with PCBM is prepared by UV polymerization. As a result, the composite film not only performs broadband reflection in NIR region, but also exhibits a strong nonlinear absorption and excellent optical limiter properties in visible region, which proves the film's potential application in laser damage prevention.